Business cycles and energy intensity. Evidence from emerging economies - Tinghui Li; Xue Li; Gaoke Liao (Borsa Istanbul Review, 2022)
Reducing energy intensity and coping with climate change are important policy issues that face all countries. This study examines the impact of business cycles (recessions and expansions) on energy intensity in sixteen emerging countries in 1990–2014. We find that during periods of economic expansion (recessions), business cycles reduce (increase) energy intensity. We also study the moderating effect of foreign direct investment (FDI) between business cycles and energy intensity and find that FDI lowers (raises) energy intensity in countries with high (low) level economic development. In addition, this study finds a nonlinear relationship between business cycles and energy intensity. Policy implications of the findings are discussed.